A Simple Discriminating p‐tert‐Butylcalix[4]arene Thiospirolactam Rhodamine B Based Colorimetric and Fluorescence Sensor for Mercury Ion and Live Cell Imaging Applications. Issue 16 (24th April 2018) - Anandababu, Ambigapathi; Anandan, Sambandam; Ashokkumar, Muthupandian
Abstract: The inherent amphiphilic property of modified p‐tert‐butylcalix[4]arene thiospirolactam rhodamine b based ligand for effective colorimetric Off‐On sensor for Hg 2+ ion in neutral aqueous condition, has been investigated by electronic spectroscopic techniques. This ligand discriminates chronic poisonous Hg 2+ ion over various alkali, alkaline earth and transition metal ions due to the presence of thiospirocyclic moiety. The ligand shows an association constant of 3.63 X 10 5 M ‐1 and a detection limit 9.65 X 10 ‐9 M for Hg 2+ ion. This ligand is also capable of penetrating into HeLa cell, which could be used to detect Hg 2+ ions in biological system using a fluorescence imaging technique. Abstract : In this work we focus synthesis of new p‐tert‐butylcalix[4]arene thiospirolactam rhodamine b based ligand and sensing of Hg 2+ ion calorimetrically through Off‐On mechanism in aqueous medium. Mercury induced ring opening of thiospirolactam moiety is the key strategy of this sensor due to sulfurphilic nature of mercury. This sensor discriminates chronic poisonous Hg 2+ ion over various alkali, alkaline earth and transition metal ions and sense effectively and selectively Hg 2+ ion in neutral aqueous condition, has been investigated by electronic spectroscopic techniques. The ligand shows detection limit 9.65 nM for Hg 2+ ion. This ligand is also suitable to penetrate into HeLa cell, which could be used to detect Hg 2+ ions in biological system using a fluorescence imaging technique.